2021
DOI: 10.7759/cureus.14483
|View full text |Cite
|
Sign up to set email alerts
|

A Cytological Study Enlightening the Unseen Effects of Concomitant Chemoradiotherapy in Contralateral Normal Buccal Mucosa of Oral Squamous Cell Carcinoma Patients

Abstract: Background/objectivesIn patients receiving concomitant chemoradiotherapy (CCRT) as a treatment for oral squamous cell carcinoma (OSCC), cytological changes were seen not only in neoplastic epithelial cells but the nonneoplastic epithelial cells are also affected, resulting in cytopathological atypical changes. The present study was designed to observe oral epithelial atypical cytopathologic changes induced in contralateral normal buccal mucosa in OSCC patients receiving CCRT. MethodsThe study included 150 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Histologically, the lesion passes from reactive epithelial changes (such as hyperkeratosis, hyperplasia and acanthosis) or pre-neoplastic changes (including mild, moderate and severe dysplasia) prior to the establishment of an invasive carcinoma (Neville et al, 2009;Rivera, 2012). In a case-control study, Minhas et al (2021) have reported that cytological changes were observed not only in neoplastic epithelial cells but the nonneoplastic epithelial cells are also affected, resulting in cytopathological atypical changes in patients receiving concomitant chemoradiotherapy (CCRT) as a treatment for oral squamous cell carcinoma (OSCC), Nuclear atypia features were higher on the 17th day and end of treatment; whereas, epithelial atypia was mainly observed on the 17th day of CCRT (40 %). Atypia was not observed in any control group.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the lesion passes from reactive epithelial changes (such as hyperkeratosis, hyperplasia and acanthosis) or pre-neoplastic changes (including mild, moderate and severe dysplasia) prior to the establishment of an invasive carcinoma (Neville et al, 2009;Rivera, 2012). In a case-control study, Minhas et al (2021) have reported that cytological changes were observed not only in neoplastic epithelial cells but the nonneoplastic epithelial cells are also affected, resulting in cytopathological atypical changes in patients receiving concomitant chemoradiotherapy (CCRT) as a treatment for oral squamous cell carcinoma (OSCC), Nuclear atypia features were higher on the 17th day and end of treatment; whereas, epithelial atypia was mainly observed on the 17th day of CCRT (40 %). Atypia was not observed in any control group.…”
Section: Discussionmentioning
confidence: 99%